Grafting Polytetrafluoroethylene Micropowder via in Situ Electron Beam Irradiation-Induced Polymerization - Wang, Hui (Polymers (Basel), 2018)
Decreasing the surface energy of polyacrylate-based materials is important especially in embossed holography, but current solutions typically involve high-cost synthesis or encounter compatibility problems. Herein, we utilize the grafting of polytetrafluoroethylene (PTFE) micropowder with poly (methyl methacrylate) (PMMA). The grafting reaction is implemented via in situ electron beam irradiation-induced polymerization in the presence of fluorinated surfactants, generating PMMA grafted PTFE micropowder (PMMA–g–PTFE). The optimal degree of grafting (DG) is 17.8%. With the incorporation of PMMA–g–PTFE, the interfacial interaction between polyacrylate and PTFE is greatly improved, giving rise to uniform polyacrylate/PMMA–g–PTFE composites with a low surface energy. For instance, the loading content of PMMA–g–PTFE in polyacrylate is up to 16 wt %, leading to an increase of more than 20 degrees in the water contact angle compared to the pristine sample. This research paves a way to generate new polyacrylate-based films for embossed holography.